Nelegálně v USA - Adriana Kábová (AntropoWebzin)
Illegal migration is a topic discussed in Czech environment mostly in connection with immigrants heading into the Czech Republic. The topic of this report will be to point out the phenomenon of irregular migration from the Czech Republic into the United States and the way the vague legal status of a migrant affects his everydayness. The article describes the client system as a specific type of social network.